Flame-retardant bio-based copolymer resin based on PT-fa and preparation method of flame-retardant bio-based copolymer resin
Thermal polymerization of the low-melting point benzoxazine monomer PT-fa and BA-a resin was synthesized by solvent-free method to form a copolymer resin with high heat resistance and high flame retardancy, solving the green and environmental protection problems caused by the high melting point of the monomer The problem of uneven blending with solid-liquid can achieve high-performance flame-retardant bio-based copolymer resin.
Patent Information
- Application Number
- CN202411490118.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-24
AI Technical Summary
In the prior art, when the benzoxazine resin based on biomass raw materials is synthesized in solvent-free method, it cannot meet the green and environmental protection requirements due to the high melting point of the monomer, and there is a problem of uneven solid-liquid blending, which affects the stability of the resin. and molding performance.
The low melting point benzooxazine monomer PT-fa was synthesized by solvent-free method using hydroxytyrosol and furfuramine as raw materials, and thermally polymerized with BA-a resin to form a copolymer resin with high heat resistance and high flame retardancy ( PT-fa/BA-a), overcomes the problem that PT-fa alone cannot form.
The uniform blending and thermal stability of low melting points of PT-fa and BA-a is achieved, which significantly improves the heat resistance and flame retardant properties of copolymerized resins. At the same time, the problem of PT-fa cannot be formed is solved, and the excellent processing technology is formed. flame retardant bio-based copolymer resin.
Smart Images

Figure CN119241793A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional polymer materials, and in particular to a flame retardant bio-based copolymer resin based on PT-fa and a preparation method thereof. Background Art
[0002] Benzoxazine has the advantages of strong molecular designability, excellent heat resistance and flame retardancy, and good dielectric properties, so it is widely used in electronic packaging, aerospace and other fields. Among them, bisphenol A-aniline benzoxazine BA-a has become the most successful commercial benzoxazine due to its simple synthesis process and low cost. However, BA-a has the problem of poor heat resistance and flame retardancy.
[0003] At present, the conventional method for solving the problems of heat resistance and flame retardancy of BA-a is to copolymerize BA-a resin with other high-performance benzoxazine resins to achieve modification. This type of method also has the advantage that while improving the performance of the copolymerized resin, there is no compatibility problem. For example, existing document 1 (Wang T, Wang Z, Pan ZC, et al. Synthesis of novel allylamine-fluorene based benzoxazine and its copolymerization with typical benzoxazine: Curing behavior and thermal properties [J]. New Journal of Chemistry. 2024-10-12) copolymerizes BA-a with fluorene-containing benzoxazine monomers, which significantly improves the heat resistance of the copolymerized resin (Tg increased by 15 ° C, Tdi increased by 12.7%). However, the technical problem with this technical solution is that the synthetic raw materials of fluorene-based benzoxazine monomers come from fossil resources, which does not meet the requirements of green and environmental protection.
[0004] However, there is no report on the synthesis of benzoxazine copolymerized with BA-a based on biomass raw materials based on solvent-free method. For example, although the existing document 2 ([1] Shitong, Ren, Xiangyan, et al. A fully bio-based benzoxazine as latent catalyst for bisphenol A / aniline-based benzoxazine-Science Direct [J]. Materials Today Communications, 20 (C): 100568-100568.2024-10-13) uses biomass raw materials to synthesize benzoxazine monomers, the solvent used in this technical solution is ethyl acetate.
[0005] The advantages of the solvent-free method include energy saving, greenness and environmental protection, but the reason why it has not been realized yet is that the solvent-free method requires the raw materials and products to have low melting points. However, the benzoxazine resins that can meet the application requirements currently have high rigidity structures, resulting in high melting points of their synthetic raw materials and monomers, making it impossible to use the solvent-free method for synthesis. For example, existing document 3 (An apigenin-based bio-benzoxazine with three polymerizable functionalities: sustainable synthesis, thermal latent polymerization, and excellent thermal properties of its thermosets, Polymer Chemistry, 2020, 11, 5800-5809) uses apigenin and furfurylamine as the main raw materials to synthesize an all-biomass benzoxazine monomer, and its cured resin has an initial thermal decomposition temperature Tdi of 384°C, a heat release capacity HRC of 20.2 J / g·K, and a total heat release THR of 9.4 kJ / g. The molecules used in this technical method have a highly rigid structure, and the melting point of its monomer is as high as 174°C. This property determines that the monomer cannot be prepared by a solvent-free synthesis method. This technical solution adopts a solvent method for preparation, specifically using toluene as the reaction medium.
[0006] Therefore, the problem of the technical solution is that toxic solvents are used as raw materials on the surface. In addition to causing environmental pollution problems under high temperature reaction conditions, toxic solvents are also present in residual materials, affecting the subsequent application range. Therefore, it can be confirmed that the fundamental problem of this type of technical solution is that due to the basic properties of its monomers, it is impossible to adopt a solvent-free method for preparation, thereby being unable to meet the requirements of green environmental protection. For example, existing document 4 (Smart and sustainable design of latent catalyst-containing benzoxazine-bio-resins and application studies) uses high melting point green benzoxazine and is copolymerized with BA-a in a solvent-free blending method. Although the technical solution adopts a solvent-free blending method, due to the presence of solid-liquid blending, there is a phenomenon of uneven mixing, which then affects the stability of the resulting resin.
[0007] In order to solve the above-mentioned solid-liquid blending problem, it is necessary to use green benzoxazine with a low melting point and copolymerize it with BA-a to prepare a resin to overcome it. Therefore, the applicant of the present invention uses hydroxytyrosol and furfurylamine as raw materials and synthesizes a new low-melting point benzoxazine PT-fa by a solvent-free method. In addition, the cured resin Poly (PT-fa) has high heat resistance and high flame retardancy - the heat release capacity HRC is 21.3J / g·K, and the total heat release THR is 2.9kJ / g, that is, it has been tested that the HRC and THR of Poly (PT-fa) are lower than the HRC and THR values of the cured resin of the existing all-bio-based benzoxazine synthesized by the solvent-free method, and has excellent flame retardant properties. However, the applicant found in the research process that when PT-fa is used alone for the curing reaction, due to the violent curing reaction process, a large number of pores appear in the cured resin, that is, the technical solution has a technical problem that cannot be formed, that is, PT-fa cannot be used alone. Summary of the invention
[0008] In view of the deficiencies in the prior art, the present invention provides a flame retardant bio-based copolymer resin based on PT-fa and a preparation method thereof.
[0009] The basic principle of this method is that, first, hydroxytyrosol, furfurylamine and paraformaldehyde are used as raw materials to prepare low-melting-point bio-based benzoxazine monomer PT-fa, and the solvent-free synthesis can be smoothly implemented through the low-melting-point benzoxazine monomer, and the mixture with BA-a resin is more uniform, thereby ensuring the performance stability of the copolymer resin; then, PT-fa and BA-a are blended by solvent-free method, and further thermally polymerized to obtain the copolymer resin. The method of the present invention not only significantly improves the heat resistance and flame retardancy of BA-a resin, but also solves the problem that PT-fa cannot be molded.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] A flame retardant bio-based copolymer resin based on PT-fa, wherein a mixed resin is obtained by using a bio-based benzoxazine monomer PT-fa and a bisphenol A-aniline type benzoxazine BA-a as raw materials, and then the mixed resin is thermally cured to obtain a flame retardant bio-based copolymer resin Poly (PT-fa / BA-a) based on PT-fa, wherein the obtained copolymer resin has high thermal stability and high flame retardancy;
[0012] The PT-fa is prepared by a solvent-free synthesis method using hydroxytyrosol, furfurylamine and paraformaldehyde as raw materials, and the obtained monomer has high purity;
[0013] The glass transition temperature T of the Poly (PT-fa / BA-a) g 180-300℃;
[0014] The temperature T at which the Poly (PT-fa / BA-a) loses 5% of its weight under nitrogen atmosphere di The residual carbon rate at 328-340℃ and 800℃ is Y c 38-60%;
[0015] The heat release capacity HRC of the Poly (PT-fa / BA-a) is 80-175 J / g·K, and the total heat release THR is 10-21 kJ / g.
[0016] 5. A method for preparing a flame retardant bio-based copolymer resin based on PT-fa, comprising the following steps:
[0017] Step 1, preparation of bio-based benzoxazine monomer PT-fa, hydroxytyrosol, furfural amine and paraformaldehyde satisfying a certain amount of substance ratio, hydroxytyrosol, furfural amine and paraformaldehyde are mixed, and a Mannich condensation reaction is carried out under certain conditions by a solvent-free method. After the reaction is completed, the bio-based benzoxazine monomer is obtained after recrystallization and drying, which is referred to as PT-fa;
[0018] In the step 1, the molar ratio of hydroxytyrosol, furfurylamine and paraformaldehyde is 1:2:4;
[0019] In the step 1, the conditions for the Mannich condensation reaction are: in an oil bath and under stirring conditions, the reaction temperature is 110° C. and the reaction time is 6 h;
[0020] In the step 1, the recrystallization operation is carried out in ethanol;
[0021] Step 2, preparation of a flame retardant bio-based copolymer resin based on PT-fa, first, under certain conditions, completely melt the PT-fa obtained in step 1 and bisphenol A-aniline benzoxazine BA-a to obtain a mixed resin, then place the molten mixed resin in a mold, and finally, solidify the mixed resin to obtain a flame retardant bio-based copolymer resin based on PT-fa, referred to as Poly (PT-fa / BA-a);
[0022] In the step 2, the mass ratio of PT-fa to BA-a is 2:(3-38); the conditions for completely melting PT-fa and BA-a to obtain a mixed resin are: under stirring conditions, the heating temperature is 115-140° C., and the heating time is 5-30 min;
[0023] In step 2, the curing conditions are divided into 4 stages:
[0024] Stage 1: curing temperature is 180°C and curing time is 1h;
[0025] Stage 2: curing temperature is 200°C and curing time is 1h;
[0026] Stage 3: curing temperature is 220°C and curing time is 1h;
[0027] Stage 4 is a curing temperature of 240°C and a curing time of 2 hours.
[0028] The technical effect of the present invention can be known through the following tests:
[0029] The HRMS test results show that the mass-to-charge ratio is 397.1740, which is consistent with [C 22 H 25 N2O5] + The difference from the theoretical value of mass-to-charge ratio of 397.1764 is negligible. The test results show that PT-fa was successfully synthesized.
[0030] The FTIR test results show that PT-fa contains characteristic peaks of CN, COC, oxazine ring, ethylene in ethanol group and hydroxyl peak. The test results show that PT-fa was successfully synthesized.
[0031] go through1 The H NMR test results show that PT-fa contains the characteristic hydrogen spectrum of furan ring, benzene ring, methylene on oxazine ring, and methylene and ethylene connecting furan ring, without other obvious impurity peaks. The test results show that PT-fa was successfully synthesized and has high purity.
[0032] go through 13 The C NMR test results show that PT-fa contains the characteristic carbon spectra of the methylene on the oxazine ring, the methylene connected to the furan ring, and the ethylene. The test results show that PT-fa was successfully synthesized.
[0033] The DSC test results show that the curing exothermic peak of PT-fa is narrow and sharp, and its curing reaction is violent, which directly leads to excessive local temperature, resulting in sample decomposition and bubble generation. The curing exothermic peak of (PT-fa / BA-a)-40 is wide and short. The copolymerization of PT-fa and BA-a can effectively avoid the problem of excessive local temperature and sample decomposition due to violent curing reaction.
[0034] The results of macroscopic morphology tests show that: Poly(PT-fa) resin contains a large number of bubbles and cannot be molded, that is, it does not have moldability. Poly(PT-fa / BA-a)-40 is a tough black solid without bubbles, that is, it has moldability.
[0035] The FTIR test results show that the characteristic peaks of CN, COC and oxazine ring disappear. The test results show that
[0036] (PT-fa / BA-a)-40 undergoes a ring-opening cross-linking reaction to form a cured resin Poly(PT-fa / BA-a)-40.
[0037] The TGA test results show that the temperature T at which Poly(PT-fa / BA-a)-40 loses 5% of its weight under nitrogen atmosphere is di The carbon residue rate Y at 338℃ and 800℃ c The test results show that Poly(PT-fa / BA-a)-40 has good thermal stability.
[0038] The DMA test results show that the glass transition temperature of Poly(PT-fa / BA-a)-40 is T g The test results show that Poly(PT-fa / BA-a)-40 has good heat resistance.
[0039] The MCC test results show that the heat release capacity HRC of Poly(PT-fa / BA-a)-40 is 110.8J / g·K, and the total heat release THR is 13.9kJ / g. The test results show that Poly(PT-fa / BA-a)-40 has excellent flame retardant properties.
[0040] Compared with the prior art, the present invention has the following advantages:
[0041] 1. The present invention uses biomass (hydroxytyrosol, furfurylamine) as the main raw materials, and synthesizes and purifies bio-based benzoxazine monomer (PT-fa) without solvent or in green solvent ethanol. The PT-fa synthesized by the present invention has excellent processing technology and a melting point (Tm) of 113.8°C;
[0042] 2. The benzoxazine resin (poly(PT-fa)) prepared by the present invention has a Tdi of 326°C, a carbon residue rate (Yc) of 65.8% at 800°C, an HRC of 21.3 J / g·K, and a THR of 2.9 kJ / g, wherein the HRC and THR values are lower than those of all the curing resins of all-bio-based benzoxazine synthesized by the solvent-free method; poly(PT-fa) has not only good thermal stability but also outstanding flame retardancy;
[0043] 3. The present invention utilizes the low melting point of PT-fa, blends it with commercial benzoxazine monomer (BA-a) in a molten state, and prepares a copolymer resin Poly (PT-fa / BA-a), which overcomes the defect that poly (PT-fa) cannot be molded;
[0044] 4. When the PT-fa content of the copolymer resin of the present invention is 40%, that is, Poly(PT-fa / BA-a)-40, compared with the commercial resin, its Tg, Tdi and Tg, Tdi and Yc are increased by 78.6°C, 10°C and 11.8%, respectively; HRC and THR are reduced by 33% and 35%, respectively; the addition of PT-fa significantly improves the heat resistance and flame retardancy of the commercial resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 is the synthesis reaction formula and chemical structure formula of the bio-based benzoxazine monomer (PT-fa) in Example 1 of the present invention;
[0046] Figure 2 is the Fourier transform infrared (FTIR) spectrum of PT-fa in Example 1 of the present invention;
[0047] Figure 3 is the hydrogen nuclear magnetic resonance (1H NMR) spectrum of PT-fa in Example 1 of the present invention;
[0048] Figure 4 is the carbon nuclear magnetic resonance (13C NMR) spectrum of PT-fa in Example 1 of the present invention;
[0049] Figure 5 is the high resolution mass spectrum (HRMS) of PT-fa in Example 1 of the present invention;
[0050] Figure 6 The differential scanning calorimetry (DSC) curves of (PT-fa / BA-a)-40, PT-fa, BA-a, and (PT-fa / BA-a)-20 in Example 1, Comparative Example 1, Comparative Example 2, and Example 2 of the present invention are shown;
[0051] Figure 7 The macroscopic morphology photos of Poly(PT-fa / BA-a)-40, Poly(BA-a), and Poly(PT-fa / BA-a)-20 in Example 1, Comparative Example 2, and Example 2 of the present invention are shown in FIG.
[0052] Figure 8 The FTIR spectra of Poly(PT-fa / BA-a)-40 and Poly(PT-fa / BA-a)-20 in Examples 1 and 2 of the present invention are
[0053] Fig. 9 The thermogravimetric (TGA) curves of Poly(PT-fa / BA-a)-40, Poly(BA-a), and Poly(PT-fa / BA-a)-20 in Example 1, Comparative Example 2, and Example 2 of the present invention;
[0054] Fig.10 The dynamic mechanical analysis (DMA) curves of Poly(PT-fa / BA-a)-40, Poly(BA-a), and Poly(PT-fa / BA-a)-20 in Example 1, Comparative Example 2, and Example 2 of the present invention;
[0055] Fig.11 The heat release rate (HRR)-temperature curves of the bio-based benzoxazine Poly(PT-fa / BA-a)-40, Poly(BA-a), and Poly(PT-fa / BA-a)-20 in the micro combustion calorimetry (MCC) test of Example 1, Comparative Example 2, and Example 2 of the present invention;
[0056] Fig.12 This is a macroscopic morphology photograph of Poly(PT-fa) in Comparative Example 1 of the present invention;
[0057] Fig.13 is the TGA curve of Poly(PT-fa) in Comparative Example 1 of the present invention;
[0058] Fig.14 is the HRR-temperature curve of the MCC test of the bio-based benzoxazine Poly (PT-fa) in Comparative Example 1 of the present invention;
[0059] Fig.15 is the HRR-temperature curve in the MCC test of the bio-based benzoxazine Poly(PT-fa / BA-a)-10 in Example 3 of the present invention;
[0060] Fig.16 This is the HRR-temperature curve of the bio-based benzoxazine Poly(PT-fa / BA-a)-5 in the MCC test in Example 4 of the present invention. DETAILED DESCRIPTION
[0061] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0062] Example 1
[0063] A method for preparing a flame retardant bio-based copolymer resin based on PT-fa comprises the following steps:
[0064] Step 1, preparation of bio-based benzoxazine monomer PT-fa, with the molar ratio of hydroxytyrosol, furfurylamine and paraformaldehyde being 1:2:4, 10.962g hydroxytyrosol, 13.809g furfurylamine and 8.542g paraformaldehyde are mixed, that is, the total mass of the raw materials is 33.313g, and a Mannich condensation reaction is carried out under the conditions of a solvent-free method, an oil bath and stirring, a reaction temperature of 110°C, and a reaction time of 6h. After the reaction is completed, after recrystallization and drying, a bio-based benzoxazine monomer, referred to as PT-fa, can be obtained;
[0065] The recrystallization operation is carried out in ethanol.
[0066] In order to prove the successful synthesis of PT-fa, HRMS test was performed. The test results are shown in Figure 1 As shown, the measured value of the mass-to-charge ratio is 397.1740, which is consistent with [C 22 H 25 N2O5] + The difference from the theoretical value of mass-to-charge ratio of 397.1764 is negligible. The test results show that PT-fa was successfully synthesized.
[0067] In order to further prove the successful synthesis of PT-fa and confirm the composition of PT-fa, FTIR test was performed. The test results are as follows Figure 2 As shown, PT-fa contains characteristic peaks of CN, COC, oxazine ring, ethylene in ethanol group and hydroxyl peak. The test results show that PT-fa was successfully synthesized.
[0068] In order to further prove the successful synthesis and purity of PT-fa, 1 H NMR testing and 13 C NMR test.
[0069] 1 The results of H NMR tests are as follows Figure 3 As shown, PT-fa contains the characteristic hydrogen spectrum of furan ring, benzene ring, methylene on oxazine ring, methylene and ethylene connecting furan ring, and no other obvious impurity peaks. The test results show that PT-fa was successfully synthesized and has high purity.
[0070] 13 C NMR test results are as follows Figure 4 As shown, PT-fa contains the characteristic carbon spectrum of the methylene group on the oxazine ring, the methylene group connected to the furan ring, and the ethylene group. The test results show that PT-fa was successfully synthesized.
[0071] In order to prove the yield of PT-fa, the mass of PT-fa obtained in step 1 was weighed. The mass of PT-fa was 28.019 g, and it was calculated that the yield of PT-fa was 84.1%.
[0072] The bio-based benzoxazine monomer PT-fa was synthesized for the first time and there is no existing synthesis reaction formula. According to the above HRMS test, FTIR test and NMR test, it can be confirmed that the synthesis reaction formula of PT-fa is as follows: Figure 5 As shown, PT-fa is synthesized by a solvent-free method using hydroxytyrosol, furfurylamine and paraformaldehyde as reactants and a Mannich condensation reaction under heating conditions.
[0073] Since PT-fa was synthesized for the first time and there is no existing thermal performance data, DSC test was performed to prove the thermal performance of PT-fa, that is, its processing performance. Figure 6 As shown, the melting point of PT-fa is 113.8°C and the peak curing temperature is 224.9°C. The test results show that PT-fa has a lower melting point and curing temperature, which directly leads to the solvent-free synthesis method of PT-fa, that is, PT-fa has excellent processing properties.
[0074] Step 2, preparation of a flame retardant bio-based copolymer resin based on PT-fa. First, under stirring conditions, at a heating temperature of 130° C. and a heating time of 10 min, 5.713 g of the PT-fa obtained in step 1 and 8.570 g of bisphenol A-aniline type benzoxazine BA-a are completely melted to obtain a mixed resin. Then, the molten mixed resin is placed in a mold. Finally, the mixed resin is cured to obtain a flame retardant bio-based copolymer resin based on PT-fa, referred to as Poly (PT-fa / BA-a). The amount of PT-fa added in the copolymer resin obtained in specific Example 1 is 40 wt.%, so it is referred to as Poly (PT-fa / BA-a) -40.
[0075] The curing is divided into 4 stages:
[0076] Stage 1: curing temperature is 180°C and curing time is 1h;
[0077] Stage 2: curing temperature is 200°C and curing time is 1h;
[0078] Stage 3: curing temperature is 220°C and curing time is 1h;
[0079] Stage 4 is a curing temperature of 240°C and a curing time of 2 hours.
[0080] In order to prove that Poly(PT-fa / BA-a)-40 has the characteristics of being moldable, DSC test was carried out. The test results are as follows Figure 6 As shown in the figure, the curing exothermic peak of (PT-fa / BA-a)-40 is wide and short. The test results show that the curing reaction of PT-fa / BA-a)-40 is mild, which can effectively avoid the problem of excessive local temperature due to the violent curing reaction, thus causing the sample to decompose.
[0081] Therefore, in order to further prove the molding performance of Poly(PT-fa / BA-a)-40, macroscopic morphology test was carried out. Figure 7 As shown, Poly(PT-fa / BA-a)-40 is a tough black solid without bubbles, which means it has formability.
[0082] In order to prove the successful preparation of Poly(PT-fa / BA-a)-40, FTIR test was performed. The test results are as follows Figure 8 As shown, the characteristic peaks of CN, COC and oxazine ring disappeared, which proved that the oxazine ring underwent a ring-opening cross-linking reaction to form a cured resin Poly(PT-fa / BA-a)-40.
[0083] In order to prove the thermal stability of Poly(PT-fa / BA-a)-40, a thermal gravimetric analysis (TGA) test was performed. Fig. 9 As shown, the temperature T when the thermal weight loss of Poly(PT-fa / BA-a)-40 is 5wt.% in a nitrogen atmosphere is di The carbon residue rate Y at 338℃ and 800℃ c The test results show that Poly(PT-fa / BA-a)-40 has good thermal stability.
[0084] In order to prove that Poly(PT-fa / BA-a)-40 has heat resistance, dynamic thermal mechanical analysis (DMA) test was performed. The test results are as follows: Fig.10 As shown, the glass transition temperature T of Poly(PT-fa / BA-a)-40 g The test results show that Poly(PT-fa / BA-a)-40 has good heat resistance.
[0085] In order to prove that Poly(PT-fa / BA-a)-40 has flame retardant properties, a micro combustion calorimetry MCC test was conducted. The test results are as follows Fig.11 As shown in the figure, the heat release capacity HRC of Poly(PT-fa / BA-a)-40 is 110.8J / g·K, and the total heat release THR is 13.9kJ / g. The test results show that Poly(PT-fa / BA-a)-40 has excellent flame retardant properties.
[0086] In order to further demonstrate the moldable properties of Poly (PT-fa / BA-a), Comparative Example 1 is provided, which is a bio-based benzoxazine resin cured with PT-fa alone, that is, to demonstrate the role of BA-a in the copolymer resin; at the same time, in order to demonstrate the role of PT-fa in the copolymer resin, Comparative Example 2 is provided, which is a bisphenol A-aniline type benzoxazine resin cured with BA-a alone.
[0087] It is noted that bisphenol A-aniline benzoxazine resin Poly (BA-a) is a commercial resin, and its raw material bisphenol A-aniline benzoxazine BA-a is also prepared by a solvent-free method and is commercially available.
[0088] Comparative Example 1
[0089] A method for preparing a bio-based benzoxazine resin cured by PT-fa alone, wherein the steps not specifically described are the same as those in Example 1, except that: in step 2, BA-a is not added, and a bio-based benzoxazine resin cured by PT-fa alone can be obtained, which is referred to as Poly(PT-fa).
[0090] In order to prove the molding performance of Poly(PT-fa), DSC test was carried out. The test results are as follows Figure 6As shown in the figure, the curing exothermic peak of PT-fa is narrow and sharp. The test results show that the violent curing reaction of PT-fa directly leads to excessively high local temperature, which causes the sample to decompose and generate bubbles.
[0091] In order to further prove the molding performance of Poly(PT-fa), macroscopic morphology test was carried out. The test results are as follows Fig.12 As shown, there are a lot of bubbles in the Poly(PT-fa) resin, which cannot be molded, that is, it does not have moldability.
[0092] In order to prove the thermal stability of Poly(PT-fa), TGA test was performed. The test results are as follows Fig.13 As shown, the temperature T at which Poly(PT-fa) loses 5% of its weight under nitrogen atmosphere di The residual carbon rate Y at 326℃ and 800℃ c The test results show that Poly(PT-fa) has good thermal stability.
[0093] In order to prove that Poly(PT-fa) has flame retardant properties, a micro combustion calorimetry MCC test was performed. The test results are as follows Fig.14 As shown, the heat release capacity HRC of Poly(PT-fa) is 21.3J / g·K, and the total heat release THR is 2.9kJ / g. The test results show that the HRC and THR of Poly(PT-fa) are lower than the HRC and THR values of the curing resin of all-bio-based benzoxazine synthesized by the existing solvent-free method, which indicates that Poly(PT-fa) has excellent flame retardant properties.
[0094] Compared with Example 1, it can be seen that although the T di The temperature dropped by 12℃, c The flame retardant properties of Poly(PT-fa) are better than those of Poly(PT-fa / BA-a)-40. However, since Poly(PT-fa) does not have formability, it cannot meet the requirements of practical applications. Therefore, only Poly(PT-fa / BA-a)-40 can meet the practical requirements.
[0095] Comparative Example 2
[0096] A method for preparing a bisphenol A-aniline type benzoxazine resin based on BA-a alone curing, wherein the steps not specifically described are the same as those in Example 1, except that: step 1 is not required, and in step 2, PT-fa is not added, to obtain a bisphenol A-aniline type benzoxazine resin, referred to as Poly(BA-a).
[0097] The DSC test results of BA-a are as follows: Figure 1 As shown in the figure, the curing exothermic peak of BA-a is wide and short. The test results show that the curing reaction of BA-a is mild and the molding processability is good.
[0098] In order to prove the molding performance of Poly(BA-a), macroscopic morphology test was carried out. The test results are as follows Figure 7 As shown, Poly(BA-a) is a tough black solid without bubbles, that is, it has formability. Compared with Example 1, it can be seen that there is no obvious difference in the macroscopic morphology of Poly(BA-a) and Poly(PT-fa / BA-a)-40.
[0099] The TGA test results of Poly(BA-a) are as follows Fig. 9 As shown, the T of Poly(BA-a) di The residual carbon rate Y at 328℃ and 800℃ c Compared with Example 1, the T di T relative to Poly(BA-a) di Increased by 10℃; Y of Poly(PT-fa / BA-a)-20 c Y relative to Poly(BA-a) c The results showed that the thermal stability of Poly(PT-fa / BA-a)-40 was significantly improved compared with Poly(BA-a).
[0100] The DMA test results of Poly(BA-a) are as follows Fig.10 As shown in the figure, the Tg of Poly(BA-a) is 163.5°C. Compared with Example 1, the Tg of Poly(PT-fa / BA-a)-20 is significantly increased by 78.6°C relative to the Tg of Poly(BA-a), with an increase of 48.1%. The test results show that adding PT-fa to form a copolymer resin can significantly improve the heat resistance.
[0101] The MCC test results of Poly(BA-a) are as follows Fig.11As shown, the heat release capacity HRC of Poly(BA-a) is 166.2 J / g·K, and the total heat release THR is 21.5 kJ / g. Compared with Example 1, the HRC of Poly(PT-fa / BA-a)-20 is only 66.6% of the HRC of Poly(BA-a), and the THR of Poly(PT-fa / BA-a)-20 is only 64.7% of the THR of Poly(BA-a). The test results show that adding PT-fa to form a copolymer resin can improve the flame retardant properties.
[0102] By comparing Example 1 and Comparative Example 1, it can be seen that the copolymer resin Poly(PT-fa / BA-a) formed by adding PT-fa to BA-a has significantly improved thermal stability and flame retardant properties compared to commercial Poly(BA-a).
[0103] In order to demonstrate the effect of the amount of PT-fa added on the properties of the copolymer resin, Examples 2, 3 and 4 are provided, in which the copolymer resins are prepared with the amount of PT-fa added being 40 wt.%, 10 wt.% and 5 wt.%, respectively.
[0104] Example 2
[0105] A method for preparing a flame retardant bio-based copolymer resin based on PT-fa with a PT-fa addition amount of 20wt.%, wherein the steps not specifically stated are the same as those in Example 1, except that: in the step 2, the mass ratio of PT-fa to BA-a is 20:80, that is, 6.054g PT-fa and 24.216g BA-a are blended, and the obtained flame retardant bio-based copolymer resin based on PT-fa is referred to as Poly(PT-fa / BA-a)-20.
[0106] The DSC test results of (PT-fa / BA-a)-20 are as follows Figure 6 As shown in the figure, the curing exothermic peak of (PT-fa / BA-a)-20 is wide and short. The test results show that the curing reaction of (PT-fa / BA-a)-20 is mild, which can effectively avoid the problem of excessive local temperature due to violent curing reaction, thus causing sample decomposition.
[0107] Therefore, in order to further prove the molding performance of Poly(PT-fa / BA-a)-20, macroscopic morphology test was carried out. Figure 7 As shown in the figure, Poly(PT-fa / BA-a)-40 is a tough black solid without bubbles, that is, it has formability. Compared with Example 1, it can be seen that there is no obvious difference in the macroscopic morphology of Poly(PT-fa / BA-a)-20 and Poly(PT-fa / BA-a)-40.
[0108] In order to prove the successful preparation of Poly(PT-fa / BA-a)-20, FTIR test was performed. The test results are as follows Figure 8 As shown, the characteristic peaks of CN, COC, and oxazine rings disappeared. Comparing the test results with those in step 1, it can be seen that PT-fa undergoes a ring-opening cross-linking reaction to form a cured resin Poly(PT-fa).
[0109] The TGA test results of Poly(PT-fa / BA-a)-20 are as follows Fig. 9 As shown, the T of Poly(PT-fa / BA-a)-20 di The residual carbon rate Y at 335℃ and 800℃ c Compared with Example 1, it can be seen that increasing the amount of PT-fa added can improve the thermal stability of the copolymer resin.
[0110] The DMA test results of Poly(PT-fa / BA-a)-20 are as follows Fig.10 As shown, the T of Poly(PT-fa / BA-a)-20 g The temperature is 219.3° C. Compared with Example 1, it can be seen that increasing the amount of PT-fa added can improve the heat resistance of the copolymer resin.
[0111] The MCC test results of Poly(PT-fa / BA-a)-20 are as follows Fig.11 As shown, the heat release capacity HRC of Poly(PT-fa / BA-a)-20 is 142.5 J / g·K, and the total heat release THR is 17.7 kJ / g. Compared with Example 1, increasing the amount of PT-fa added can improve the flame retardant properties of the copolymer resin.
[0112] Example 3
[0113] A method for preparing a copolymer resin based on PT-fa and BA-a with a PT-fa addition amount of 10wt.%, wherein the steps not specifically stated are the same as those in Example 1, except that: in the step 2, the mass ratio of PT-fa to BA-a is 10:90, that is, 1.534g PT-fa and 13.81g BA-a are blended, and the obtained flame-retardant bio-based copolymer resin based on PT-fa is referred to as Poly(PT-fa / BA-a)-10.
[0114] The MCC test results of Poly(PT-fa / BA-a)-10 are as follows Fig.15 As shown, the heat release capacity HRC of Poly(PT-fa / BA-a)-10 is 174.4 J / g·K, and the total heat release THR is 19.8 kJ / g. Compared with Example 1, it can be seen that reducing the amount of PT-fa added reduces the flame retardant properties of the copolymer resin.
[0115] Example 4
[0116] A method for preparing a copolymer resin based on PT-fa and BA-a with a PT-fa addition amount of 5 wt.%, wherein the steps not specifically stated are the same as those in Example 1, except that: in the step 2, the mass ratio of PT-fa to BA-a is 5:95, that is, 1.054 g PT-fa and 20.026 g BA-a are blended, and the obtained flame retardant bio-based copolymer resin based on PT-fa is referred to as Poly(PT-fa / BA-a)-5.
[0117] The MCC test results of Poly(PT-fa / BA-a)-5 are as follows Fig.16 As shown, the heat release capacity HRC of Poly(PT-fa / BA-a)-5 is 174.0 J / g·K, and the total heat release THR is 21.0 kJ / g. Compared with Example 1, it can be seen that reducing the amount of PT-fa added reduces the flame retardant properties of the copolymer resin.
[0118] It can be seen from Example 1, Example 2, Example 3 and Example 4 that as the amount of PT-fa added in BA-a increases, the thermal stability and flame retardancy of the formed copolymer resin are significantly improved; however, excessive addition will lead to a significant decrease in the molding performance of the copolymer resin. Therefore, when the addition amount of PT-fa is 40wt.%, the comprehensive performance is optimal.
Claims
1. A flame retardant bio-based copolymer resin based on PT-fa, characterized in that: A mixed resin is obtained by using bio-based benzoxazine monomer PT-fa and bisphenol A-aniline benzoxazine BA-a as raw materials. Then, the mixed resin is thermally cured to obtain a flame-retardant bio-based copolymer resin Poly (PT-fa / BA-a) based on PT-fa. The obtained copolymer resin has high thermal stability and high flame retardancy. The PT-fa is prepared by using hydroxytyrosol, furfurylamine and paraformaldehyde as raw materials through a solvent-free synthesis method, and the obtained monomer has high purity.
2. The flame retardant bio-based copolymer resin based on PT-fa according to claim 1, characterized in that: The glass transition temperature T of the Poly (PT-fa / BA-a) g It is 180-300℃.
3. The flame retardant bio-based copolymer resin based on PT-fa according to claim 1, characterized in that: The temperature T at which the Poly (PT-fa / BA-a) loses 5% of its weight under nitrogen atmosphere di The residual carbon rate at 328-340℃ and 800℃ is Y c It is 38-60%.
4. The flame retardant bio-based copolymer resin based on PT-fa according to claim 1, characterized in that: The heat release capacity HRC of the Poly (PT-fa / BA-a) is 80-175 J / g·K, and the total heat release THR is 10-21 kJ / g.
5. A method for preparing a flame retardant bio-based copolymer resin based on PT-fa, characterized in that The following steps are involved: Step 1, preparation of bio-based benzoxazine monomer PT-fa, hydroxytyrosol, furfural amine and paraformaldehyde satisfying a certain amount of substance ratio, hydroxytyrosol, furfural amine and paraformaldehyde are mixed, and a Mannich condensation reaction is carried out under certain conditions by a solvent-free method. After the reaction is completed, the bio-based benzoxazine monomer is obtained after recrystallization and drying, which is referred to as PT-fa; Step 2, preparation of flame-retardant bio-based copolymer resin based on PT-fa. First, under certain conditions, the PT-fa obtained in step 1 and bisphenol A-aniline benzoxazine BA-a are completely melted to obtain a mixed resin. Then, the molten mixed resin is placed in a mold. Finally, the mixed resin is cured to obtain a flame-retardant bio-based copolymer resin based on PT-fa, referred to as Poly (PT-fa / BA-a).
6. The preparation method according to claim 5, characterized in that: In the step 1, the molar ratio of hydroxytyrosol, furfurylamine and paraformaldehyde is 1:2:
4.
7. The preparation method according to claim 5, characterized in that: In the step 1, the conditions for the Mannich condensation reaction are: in an oil bath and under stirring conditions, the reaction temperature is 110° C. and the reaction time is 6 h; In the step 1, the recrystallization operation is carried out in ethanol.
8. The preparation method according to claim 5, characterized in that: In the step 2, the mass ratio of PT-fa to BA-a is 2:(3-38); the conditions for completely melting PT-fa and BA-a to obtain a mixed resin are: under stirring conditions, the heating temperature is 115-140° C., and the heating time is 5-30 min.
9. The preparation method according to claim 5, characterized in that: In step 2, the curing conditions are divided into 4 stages: Stage 1: curing temperature is 180°C and curing time is 1h; Stage 2: curing temperature is 200°C and curing time is 1h; Stage 3: curing temperature is 220°C and curing time is 1h; Stage 4 is a curing temperature of 240°C and a curing time of 2 hours.
Citation Information
Patent Citations
Low-temperature curable bio-based benzoxazine resin and preparation method thereof
CN110128611A
Bio-based benzoxazine organic phase change material as well as preparation method and application thereof
CN113416289A
